Digital Innovation through Instagram-Based Augmented Reality in Introduction to the SKCK Making Process for the South Sulawesi Regional Police - Rizal, Muhammad; Mursalim, Mursalim; Fajrianto, Wahyu (International Journal of Informatics, Economics, Management and Science, 2025)
Digital innovation in public services has gained significant global attention, particularly in enhancing service delivery and user engagement. This study explores the use of Instagram-based Augmented Reality (AR) as a novel approach to inform and educate the public about the procedure for obtaining a Surat Keterangan Catatan Kepolisian (SKCK) at the South Sulawesi Regional Police. Traditional methods, such as printed brochures and static websites, often fail to provide clear and accessible guidance, leading to inefficiencies and user frustration. In contrast, Instagram-based AR offers an interactive, visually engaging experience, enabling users to receive real-time, step-by-step instructions via AR filters. This approach simplifies the SKCK application process by providing dynamic and user-friendly guidance, reducing errors and time spent at police stations. A trial involving surveys and user feedback was conducted to evaluate the effectiveness of this digital tool. The results indicate that AR significantly improves user understanding, satisfaction, and engagement compared to conventional methods. This study demonstrates the potential of AR to enhance public service delivery and offers insights into the application of digital technologies in governmental processes. The proposed innovation is not only an effective solution for the SKCK process but also sets a precedent for future digital transformations in public services.